UPAYA PENINGKATAN HASIL BELAJAR CHEST PASS BOLA BASKET MELALUI VARIASI PEMBELAJARAN PADA SISWA KELAS VIII-2 SMP BAITUL AZIZ KABUPATEN DELI SERDANG TAHUN AJARAN 2017/2018 - Fadlin Amin Hia (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The research was conducted at Baitul Aziz Junior High School, Deli Serdang Regency. The time of this research was carried out on August 2017 in the 2017/2018 academic year. The subjects receiving the action in this study were students of class VIII-2 SMP Baitul Aziz Deli Serdang Regency for the 20172018 academic year, totaling 28 people. This research is in the form of CAR classroom action research, the researcher in this case is an observation of learning activities in the form of an action. The results of the first cycle test, from 28 students there were 15 students 53.57 who had achieved mastery learning, the rest 13 students 46.43 who had not achieved mastery learning. The average grade obtained was 61.30 Incomplete. The results of the second cycle test, from 28 students, it turns out that 25 students 89.28 have achieved learning mastery, only 3 students 10.72 have not achieved learning mastery.